THE DEVELOPMENT OF KASANG KULIM ZOO - Abdi, Rigo Hidayat; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The development of kasang kulim zoo by the great hall of conservation of Riau's natural resources is the building of the ministry of forests adopted by upt, everyregion in pekanbaru is called the great hall for conservation of the riau natural resources. Researchers focus research on operational development the kasang kulim zoo. The purpose of this research is figure out how to build the kasang kulim zoo operations and factors that interfered. The concept of theory is santoso's institutional theory: guidance, delivering containers, giving education and training, giving rewards. The study use qualitative methods with the approach of case studies, and using speculative sampling techniques, with datacollection techniques covering: observation, interviews and documentaries. The results how to plant operation at kasang kulim have not achieved a maximum and is not yet fully realized. There should be an increase criteria or criteria to be met by the kasang kulim zoo, which is incorporated into the ministry of forests' policy.Keyword: development, zoo